2002
DOI: 10.1074/jbc.m200086200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Classification of ADAMs Based on a Conserved Motif for Binding to Integrin α9β1

Abstract: ADAMs (a disintegrin and metalloproteases) are members of the metzincin superfamily of metalloproteases. Among integrins binding to disintegrin domains of ADAMs are ␣ 9 ␤ 1 and ␣ v ␤ 3 , and they bind in an RGDindependent and an RGD-dependent manner, respectively. Human ADAM15 is the only ADAM with the RGD motif in the disintegrin domain. Thus, both integrin ␣ 9 ␤ 1 and ␣ v ␤ 3 recognize the ADAM15 disintegrin domain. We determined how these integrins recognize the ADAM15 disintegrin domain by mutational analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
70
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(79 citation statements)
references
References 37 publications
8
70
0
1
Order By: Relevance
“…It is up-regulated in carcinoma cells (16) and may therefore dramatically influence cell-cell interactions as well as the local microenvironment at the interface between the tumor cells and the surrounding stroma. To determine the function of ADAM12, we and others have performed cell attachment assays (11,12,16,17,59). We found that rADAM12-cys is a substrate for cell attachment using syndecan(s) as the primary receptor (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…It is up-regulated in carcinoma cells (16) and may therefore dramatically influence cell-cell interactions as well as the local microenvironment at the interface between the tumor cells and the surrounding stroma. To determine the function of ADAM12, we and others have performed cell attachment assays (11,12,16,17,59). We found that rADAM12-cys is a substrate for cell attachment using syndecan(s) as the primary receptor (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Because all viruses known to use integrins as entry receptors have been shown to do so by ECM protein mimicry, we inspected all HCMV structural glycoproteins for the integrin-binding sequences LDV, DGE, RGD, NGR, RRETAWA, REDV, SDGR, YIGSR, YIGSE, RGES, RSGIY, RSGD, DRDE, and SRYD by using DNASTAR software (DNASTAR, Madison, WI). We found that all HCMV glycoproteins lack ECM-derived integrinbinding sequences, but the gB protein does contain a sequence very similar to the RX 6-8 DLXXF found in the ADAM family of proteins, which we have termed disintegrin-like (18,19). The gB sequences of 44 HCMV clinical isolates and two laboratory strains were analyzed for the presence of the disintegrin-like domain.…”
Section: The Gb Disintegrin-like Domain Is Highly Conserved Throughoutmentioning
confidence: 99%
“…ADAM members are multidomain proteins that can modulate a variety of cell-cell and cell-ECM interactions with specific (primarily) ␤1 integrin heterodimers (18). From the 30 known members of the ADAM family, a disintegrin loop domain consensus and minimum integrin recognition motif has been identified (RX 5-7 DLXXF͞L) (19).…”
mentioning
confidence: 99%
“…The RGD amino acids constitute the minimal region of several extracellular matrix proteins required for interaction with certain cell surface integrins. The RGD motif is the most common integrin recognition motif, but other RGD-independent integrin recognition motifs have also been reported (9,10). Recently, a gB disintegrin-like domain has been identified in the envelope glycoprotein B of the human cytomegalovirus by analysis of its sequence (11).…”
mentioning
confidence: 99%